2023
DOI: 10.1007/s00167-023-07637-z
|View full text |Cite
|
Sign up to set email alerts
|

Repair of medial meniscus posterior root tear is effective for root healing and cartilage regeneration in opening wedge high tibial osteotomy

Yun Seong Choi,
Moon Jong Chang,
Ji Han Lee
et al.

Abstract: Purpose This study aimed to determine whether the repair of a medial meniscus posterior root tear (MMPRT) is effective for MMPRT healing, cartilage regeneration, and clinical outcomes in opening wedge high tibial osteotomy (OWHTO). Methods This retrospective study included 80 patients who underwent OWHTO and subsequent second-look arthroscopy. The patients were divided into OWHTO-with-MMPRT-repair (n = 40) and OWHTO alone (n = 40) groups, and the healing rates (complete/partial/failure) were compared. Each gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Ke et al [20] reported that concurrent arthroscopic meniscal repair during OWH-TO did not lead to significant clinical benefits, even though an increased rate of meniscal healing was observed. Lee et al [29] and Choi et al [4] reported additional MMPRT repair in OWHTO meniscal healing rates but not clinical outcomes when compared with OWHTO alone. However, clinical studies conducted thus far are limited by the subjects being older than 55 years and some even being older than 65 years, making it difficult to determine definite conclusions about meniscal repair in OWHTO [4,18,27,28].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Ke et al [20] reported that concurrent arthroscopic meniscal repair during OWH-TO did not lead to significant clinical benefits, even though an increased rate of meniscal healing was observed. Lee et al [29] and Choi et al [4] reported additional MMPRT repair in OWHTO meniscal healing rates but not clinical outcomes when compared with OWHTO alone. However, clinical studies conducted thus far are limited by the subjects being older than 55 years and some even being older than 65 years, making it difficult to determine definite conclusions about meniscal repair in OWHTO [4,18,27,28].…”
Section: Discussionmentioning
confidence: 98%
“…Lee et al [29] and Choi et al [4] reported additional MMPRT repair in OWHTO meniscal healing rates but not clinical outcomes when compared with OWHTO alone. However, clinical studies conducted thus far are limited by the subjects being older than 55 years and some even being older than 65 years, making it difficult to determine definite conclusions about meniscal repair in OWHTO [4,18,27,28]. Our study included young patients (50 years old or younger) who underwent OWHTO and MMPRT repair and demonstrated that additional MMPRT repair in young patients who underwent OWHTO improved clinical outcomes (HSS scores, Tegner scores and Lysholm scores).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some scholars have proposed the MMPRT combined with HTO procedure. 17 , 18 , 19 , 20 In the study of Huang et al., 21 25 cases of MMPRT with varus knee were treated with ATPR combined with HTO. The average follow-up was 13.0 months.…”
mentioning
confidence: 99%